Elimination of assembly induced package cracks in plastic SOIC - De Guzman, Jose Cesar; Mena, Manolo G.; Epistola, E.
Considerable amount of information and knowledge is available on moisture induced package cracking, especially on surface mount devices. During IC assembly itself, plastic packages are subject to thermal and mechanical stresses which may lead to package cracking or degrade package strength, thus making the package more susceptible to moisture effects. This study was conducted to characterize and understand assembly induced package cracking in SOIC's. Probable sources of thermal and mechanical stresses were identified by analyzing each station of the SOIC back end assembly process. Each package cracking mechanism identified was defined in terms of its associated failure modes and rootcauses. The critical areas identified include mechanical deflashing, dambar removal, lead forming, singulation and IR ink curing. Mathematical models of the cracking mechanisms in these areas were developed and used to understand process input variables that affect the tendency of a package to crack. Evaluations, simulations and failure history reviews were then done to verify and substantiate the models with actual data. Process improvements were then defined based on the assembly input variables verified to be critical to SOIC package cracking tendency. These improvements include tooling modifications which reduces stresses during assembly, prevention and assignable causes through design and system improvements and tool life evaluations which eliminate potential sources of worn out tools. Package robustness measures such as anchor holes, improved tie-bar designs v-grooves and dimples were also analyzed. Process controls, monitors, contingency measures and short looped reliability tests were likewise developed for early detection and containment package crack occurences on the line.
Keywords: Plastic integrated circuit packaging; Small-outline integrated circuit (SOIC).; Surface mount technology